ASSESSMENT OF THE AGRONOMIC VALUES OF GENETICALLY MODIFIED CMV-RESISTANT HOT PEPPER (CAPSICUM ANNUUM L.) IN KOREA - Park, Kuen Woo; Kim, Jun-Hong; Park, Sung Ok; Yang, Dong Sik (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
1.3 billion US$ annually since it is widely used for its phytochemicals with medicinal properties such as capsaicin as well as for its spicy taste. However, the cucumber mosaic virus (CMV) has declined the production of the hot pepper in Korea. To overcome the problem, the CMV-resistant hot pepper lines (H15 and B20) were introduced, transforming the coat protein (cp) gene from the isolate of CMV into the conventional hot pepper line (P2377 and P915) using Agrobacterium, respectively. The agronomic values of conventional and genetically modified (GM) lines (P2377 vs H15; P915 vs B20) were assessed on the basis of 17 items for vegetative growth (e.g., plant height, plant width, stem diameter, leaf length) and 21 items for fruit development (e.g., total harvest yield, dry weight, fruit length, stalk length, fruit colour). The hot pepper lines were seeded on the 19th of April 2007 and the transplants of each line were planted on the 23rd of May at the Deokso Research Farm in the Korea University (37° 34’ N/127° 14’ E) and they were grown under a general cultivation system for hot pepper. The experiment was performed in a completely randomized design in 3 replications. In the vegetative growth, the plant height in two conventional and two GM lines was not different, however, a GM line, B20 showed smaller leaf length and leaf width than other lines. In the fruit development, GM lines had slightly higher total number and weight of harvested fruits than conventional lines. In dry weight (%), P2377, a conventional line was not different from H15, a GM line, however, B20, a GM line showed higher dry weight than P915, a conventional line. Further studies on medicinal and nutritional quality will be performed to compare the contents of capsaicin and vitamin C in conventional and GM hot pepper lines. Acknowledgements: BioGreen 21 provided funding.